2009
DOI: 10.1007/s11547-008-0358-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced breast MR imaging of claustrophobic or oversized patients using an open low-field magnet

Abstract: In claustrophobic or oversized patients, open low-field breast MR with gadobenate dimeglumine yields good diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Michel et al found poor image quality in MR pelvimetry with a low-field open MR scanner [11]. Calabrese et al concluded that open low-field contrast-enhanced MR imaging of the breast yielded good diagnostic performance in claustrophobic or oversized patients [31]. Mehdizade et al found that diffusion-weighted MR imaging performed with a low-field open MR scanner was reliable for the evaluation of acute stroke [32].…”
Section: Discussionmentioning
confidence: 99%
“…Michel et al found poor image quality in MR pelvimetry with a low-field open MR scanner [11]. Calabrese et al concluded that open low-field contrast-enhanced MR imaging of the breast yielded good diagnostic performance in claustrophobic or oversized patients [31]. Mehdizade et al found that diffusion-weighted MR imaging performed with a low-field open MR scanner was reliable for the evaluation of acute stroke [32].…”
Section: Discussionmentioning
confidence: 99%
“…In one recent report ( 22 ), 18 (4.5%) of 397 consecutive patients referred for breast MR imaging were unable to undergo the examination owing to claustrophobia ( n = 15) or body habitus ( n = 3). These women underwent open-bore MR imaging at 0.2 T, and 86% sensitivity was observed ( 22 ). Motion-induced artifacts that result in a nondiagnostic breast MR imaging examination are more common among claustrophobic patients.…”
Section: Breast Imaging: Elevated Breast Cancer Risk and Refusal For mentioning
confidence: 99%
“…DCE-MRI provides information on morphology and vascularization of the tumor [ 16 , 17 , 18 , 19 ]. BOLD MRI gives information on blood hemoglobin oxygenation including the contribution of blood volume, hematocrit, flow, hemoglobin oxygen saturation, as well as pH, 2,3 DPG [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%